The implementation of chairside talk regarding plaque control instruction by Periodontics Residents - Rafisa, Anggun; Yubiliana, Gilang; Setiawan, Asty Samiaty (Universitas Padjadjaran, 2012)
The effort to educate patients regarding oral health maintenance can be performed through the chairside-talk. The purpose of this study was to observe the chairside-talk implementation regarding the plaque control instruction by Periodontics Residents of the Periodontics Clinic Faculty of Dentistry Universitas Padjadjaran Dental Hospital, Bandung, Indonesia. This study was a descriptive study with a survey technique. All data were collected using a checklist sheet. The results showed that 100% of residents were performing chairside-talk about plaque control instruction. As much as 86.3% from all residents performed the way of communication based on the literature’s recommendation, 81.67% preferred to teach the patient about toothbrushing directly, and 78.64% gave a direct plaque control instruction. All residents were performing the chairside-talk regarding the plaque control instructions, where the majority of them were performing the way of communication by literature recommendation, and the rest were preferred a direct toothbrushing teaching and plaque control instruction.